2016
DOI: 10.1093/humrep/dew135
|View full text |Cite
|
Sign up to set email alerts
|

Intent to treat analysis ofin vitrofertilization and preimplantation genetic screening versus expectant management in patients with recurrent pregnancy loss

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 12 publications
1
59
0
1
Order By: Relevance
“…In our retrospective study, we included patients with RM, although there have been no randomized trials evaluating the efficacy of PGT-A in RM. An intent-totreat analysis comparing PGT-A to expectant management reported that the clinical outcomes including live birth and clinical miscarriage rates, were similar between RM patients undergoing PGT-A and those receiving expectant management [61]. However, the role of aneuploidy in RM is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…In our retrospective study, we included patients with RM, although there have been no randomized trials evaluating the efficacy of PGT-A in RM. An intent-totreat analysis comparing PGT-A to expectant management reported that the clinical outcomes including live birth and clinical miscarriage rates, were similar between RM patients undergoing PGT-A and those receiving expectant management [61]. However, the role of aneuploidy in RM is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…But PGS in cases of URPL is controversial. One study showed that in cases of increased sperm aneuploidy PGS seemed to prevent miscarriages and increased the chances of a successful pregnancy [ 33 ], whereas another more recent study showed that PGS did not improve the chances of a successful pregnancy compared with expectant management [ 34 ]. However, in this latter study, sperm aneuploidy status was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Whether PGT-A may improve reproductive outcomes in these patients by reducing spontaneous abortions, time to pregnancy and aneuploid offspring and potentially increasing live birth rates remains inconclusive. Given the mounting evidence, this clearly warrants further investigation (Rubio et al 2009, Murugappan et al 2016, Esquerre-Lamare et al 2018.…”
Section: Preimplantation Genetic Testing For Aneuploidy (Pgt-a) In Pamentioning
confidence: 96%